Do soil fertilization and forest canopy foliage affect the growth and photosynthesis of Amazonian saplings? - Magalhães, Nilvanda dos Santos; Marenco, Ricardo Antonio; Camargo, Miguel Angelo Branco (Scientia Agricola, 2014)
Most Amazonian soils are highly weathered and poor in nutrients. Therefore, photosynthesis and plant growth should positively respond to the addition of mineral nutrients. Surprisingly, no study has been carried out in situ in the central Amazon to address this issue for juvenile trees. The objective of this study was to determine how photosynthetic rates and growth of tree saplings respond to the addition of mineral nutrients, to the variation in leaf area index of the forest canopy, and to changes in soil water content associated with rainfall seasonality. We assessed the effect of adding a slow-release fertilizer. We determined plant growth from 2010 to 2012 and gas exchange in the wet and dry season of 2012. Rainfall seasonality led to variations in soil water content, but it did not affect sapling growth or leaf gas exchange parameters. Although soil amendment increased phosphorus content by 60 %, neither plant growth nor the photosynthetic parameters were influenced by the addition of mineral nutrients. However, photosynthetic rates and growth of saplings decreased as the forest canopy became denser. Even when Amazonian soils are poor in nutrients, photosynthesis and sapling growth are more responsive to slight variations in light availability in the forest understory than to the availability of nutrients. Therefore, the response of saplings to future increases in atmospheric [CO2] will not be limited by the availability of mineral nutrients in the soil.